The effects of Juniperi fructus essential oil and vacuum packing on the shelf life of rainbow trout fillets during storage at 2±1°C - Özpolat, Emine (Cellular and Molecular Biology Association, 2024)
We hypothesized that the combined effect of vacuum packaging and Juniperi fructus essential oil addition would increase shelf life. Six different treatments were tested. The effects of the different concentrations of J. fructus essential oil (0%, 0.3% and 0.6%) and packing method (non-vacuum and vacuum) on the fish (Oncorhynchus mykiss) fillets of stored 4±1 °C were investigated in terms of its microbiological (mesophilic aerobic bacteria and yeast-mold), chemical (pH, total volatile alkaline nitrogen (TVB-N), thiobarbituric acid (TBA value)) and sensory quality. The results showed that J. fructus essential oil had a positive significant effect on quality parameters (p<0.05). In conclusion, based primarily on sensory, TVB-N and mesophilic bacteria data the shelf-life of fresh rainbow trout was 4 days (non-vacuum packaged), 13 days (vacuum packaged), 19 and 28 days treated with J. fructus oil (0.3 and 0.6%, v/w) under vacuum packaged, respectively. J. fructus essential oil application and vacuum packaging; extended the shelf life of fish fillets by an average of 15 days. The combined use of J. fructus essential oil and packaging techniques could form the basis for new studies. © 2024 Cellular and Molecular Biology Association. All rights reserved.
Keywords: Essential Oil; Fish; J. fructus; Microbiological Quality; Vacuum Packaging